OPTIMASI RUTE PENGANGKUTAN SAMPAH DI KOTA LAMONGAN DENGAN MENGGUNAKAN METODE SAVING MATRIX - Wardatul Jannah (Program Studi Perencanaan Wilayah dan Kota, Fakultas Teknik, Universitas Semarang, 2020)
The system and transport of waste is one of the most expensive elements of waste management system in city. According to Apaydin (2007), the system and transport of waste requires about 85% of the total waste management system. Meanwhile, according to Damanhuri (2010) transportation costs of waste is 50% - 60% of the total cost of waste management. Limitations of funds allocated by the Lamongan District Government for waste management is another problem that adds to the complexity of waste problems, especially by means of waste transport. The impact is waste accumulation in some areas. This research is conducted to give recommendation of waste transportation route optimally using saving matrix method in the Lamongan city. Saving Matrix method is one of the methods used to determine the optimal route of waste transportation by minimizing the distance and travel time based on the transport load so that the shortest route and minimum transportation cost are obtained. This research resulted 14 routes of waste transportation at Lamongan City with total distance 120.24 km with total time 180.33 minutes. Total cost monthly is Rp. 9.288.540, -. So from the use of saving matrix method can save costs Rp. 656.625- per month or Rp. 7.879.500 - per year.